1998
DOI: 10.1007/s000180050213
|View full text |Cite
|
Sign up to set email alerts
|

Some cellular and molecular properties of abscisic acid: its particular involvement in growing plant roots

Abstract: microsurgical experiments, light effects), applied ABA on Abstract. Several characteristics of the plant hormone abscisic acid (ABA) are critically discussed, more or less elongating roots, ABA and indol-3yl acetic acid (IAA) directly, in relation to the extension of root cells. A few interactions (root growth, proton extrusion, hormone transport, auxin herbicides), ABA effect on the root cell topics have been selected: some biochemical characteriscycle, ABA and drought cells of elongating roots [water tics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 127 publications
(148 reference statements)
0
3
0
2
Order By: Relevance
“…It has been suggested that ABA may inhibit directly or indirectly cell extension in slow‐growing roots and in the lower side of the root elongation zone during gravitropic bending (Fig. 1; Audus 1983; Pilet 1991, 1998). Accordingly, slightly higher levels of IAA and ABA were found in the lower than in the upper side of maize roots during positive gravireaction (Pilet 1991).…”
Section: Possible Role In Auxin‐regulated Root Gravireactionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that ABA may inhibit directly or indirectly cell extension in slow‐growing roots and in the lower side of the root elongation zone during gravitropic bending (Fig. 1; Audus 1983; Pilet 1991, 1998). Accordingly, slightly higher levels of IAA and ABA were found in the lower than in the upper side of maize roots during positive gravireaction (Pilet 1991).…”
Section: Possible Role In Auxin‐regulated Root Gravireactionmentioning
confidence: 99%
“…comm.). The activity of this inhibitor‐ β is ascribed to ABA (Pilet 1998). This indicates that auxin moving down from the apex induces high ethylene and ABA levels in the lateral buds, which prevent bud outgrowth.…”
Section: Possible Role In Growth Inhibition Of Lateral Budsmentioning
confidence: 99%
“…Bertell and Eliasson, 1992; Cary et al, 1995), ethylene (e.g. Cary et al, 1995, abscisic acid (for review, see Pilet, 1998), and jasmonate (Staswick et al, 1992) all have the potential to inhibit root elongation, although at the same time, other processes such as auxin-induced lateral root formation (Zolman et al, 2000) and auxin-or ethylene-induced root hair elongation (Pitts et al, 1998) can occur.* Corresponding author; e-mail muessig@mpimp-golm.mpg.de; fax 49 -331-5250.Article, publication date, and citation information can be found at www.plantphysiol.org/cgi …”
mentioning
confidence: 99%
“…Existem alguns trabalhos que indicam um efeito estimulante no alongamento celular promovido pelo ácido abscísico (PILET, 1998). Gaither et al (1975) demonstraram que o crescimento radicular de Pisum sativum foi aumentado em 29% quando houve aplicação de 1 µM de ácido abscísico.…”
Section: Dosesunclassified